Wybrane problemy kształcenia i doskonalenia kadry dla doradztwa rolniczego w wybranych krajach - Woźniak, Anna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1998)
This study reviews some problems connected with staff training and its skills improvement in the field of agricultural extension in selected countries. Author presented the objectives and tasks of the agricultural extension as well as arising demands for professional training and skills improvement by extension workers. Both forms and methods of professional development as well as organizations and institutions which promote and supply training services to extension divisions were discussed. Finally, the structure of agricultural extension together with present system of its staff training in Poland were described. Author proposed some changes in this system to make it more efficient, modern and integrated with existing training systems in the European Union.